Teachers' perceptions on the effectiveness of teacher professional development programmes : a case of Ngaka Modiri Molema District in the North West, South Africa - Phetla, Dorcas (My University, 2021)
Leaners’ performance in schools is attributed to several factors that include Teacher Profession Development (TPD) programmes provided by teachers in various schools. Teachers expressed that they do not derive much satisfaction from them.Consequently, teachers continue to use their old, ineffective methods of teaching. Informally, teachers have referred to challenges around resources, time, and expertise of trainers and modes of implementation as contributing to their dissatisfaction in the programmes. This study sought to investigate the perceptions of teachers on the TPD programmes carried out in schools by the TPD facilitators. The study was conducted using the qualitative research approach which allowed for an in-depth understanding of the phenomenon under review. Interpretive research paradigm was adopted as well as the case study research design. Six schools were purposefully selected in the district understudy; a teacher was picked to represent each school chosen. Data was collected through individual interviews. In the same vein, data collected in the interviews was deemed sufficient and rich by the researcher to conclude the project. Data was analysed and presented in themes and categories which enabled the researcher to cluster similar responses from the participants. The main findings of this study revealed that: teachers have different perceptions on the importance of TPD programmes, they also indicated that strategies such as more training time, use of technological devices during TPD training and teachers involvement in curriculum development are important in enhancing TPD programmes. The study recommended that principals should organise training seminars and workshops on the application of discipline strategies/methods, management strategies and intervention programmes. Keywords: Teachers, professional development, training and programmes
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2021
Keywords: Professional development; Training and programmes; Teachers; Teacher educators; Career development; Training